Prediction Status Nutrition using by Body Mass Index on Mobile Device - Adri Vendi Esaku (International Journal of Informatics and Communication Technology (IJ-ICT), 2015)
This paper is aim to predict nutrition status using by the Body Mass Index (BMI). BMI for men and women are obtained from the calorie needs. Calorie requirement is used to determine energy needs. The energy needs are determined by the needs of Protein, Carbohydrate, Fat, Vitamin and Mineral. The paper is made in the form of an application program using Mobile Programming. Mobile Programming by implementing Reverse Engineering. The tool used is a J2ME application on cell phone emulator having minimal CLDC, CDC 1.1, MIDP 2.0 and MIDlet. Main contribution, BMI as the simple, fast and easy to used method. BMI can be used to determine the nutrition status of individual. The benefit for individual reduce the cost of healthcare. The new result is the prediction of the nutrition status of individual using by BMI can be applied with new ways through the Mobile Application on Mobile Device, that is implemented to the cell phone. Mobile Application is a medium for the user can be accessed anytime and anywhere. It is known an application that can yield the rational decision in predicting the nutritious needs of families.